DEVELOPMENT AND INTRODUCTION OF THE SYSTEM OF INFORMATIVE SUPPORT OF MANAGEMENT PROCESSES BY PRODUCTIVE DATA - Павленко, П.М.; Дорошенко, С.О.; Трейтяк, В.В. (Proceedings of National Aviation University (archive), 2012)
The basic problems of machine-building enterprises of Ukraine, which are related to absence of single computer-integrated informative space of CASS of the production setting, are analysed. Set intercommunication of computer-integrated CASS of the production setting, which influences on an operationability and authenticity of acceptance of administrative decisions in the conditions of machine-building production. The system of informative support of processes of management of production data is offered in computer-integrated informative space of CASS of the production setting. The structural-functional chart of management of production data of machine-building production is presented. Advantages of the use of the developed system are resulted.